Spin‐resolved atomic orbital model refinement for combined charge and spin density analysis: application to the YTiO3 perovskite. Issue 2 (2nd February 2021) - Kibalin, Iurii; Voufack, Ariste Bolivard; Souhassou, Mohamed; Gillon, Béatrice; Gillet, Jean-Michel; Claiser, Nicolas; Gukasov, Arsen; Porcher, Florence; Lecomte, Claude
Abstract : A new crystallographic method to refine a spin‐resolved atomic orbital model against X‐ray and polarized neutron diffraction data is reported. Radial extension of atomic orbitals, and their orientations and populations, are obtained for each atom in the YTiO3 perovskite crystal. Abstract : A new crystallographic method is proposed in order to refine a spin‐resolved atomic orbital model against X‐ray and polarized neutron diffraction data. This atomic orbital model is applied to the YTiO3 perovskite crystal, where orbital ordering has previously been observed by several techniques: X‐ray diffraction, polarized neutron diffraction and nuclear magnetic resonance. This method gives the radial extension, orientation and population of outer atomic orbitals for each atom. The interaction term between Ti 3+, Y 3+ cations and O 2− ligands has been estimated. The refinement statistics obtained by means of the orbital method are compared with those obtained by the multipole model previously published.